Integrating computer-related technology into instructional practice at a higher learning institution in Malaysia - Malecela, Issa Omar (IIUM Journal of Educational Studies, 2018)
Malaysian Higher Learning institutions have embraced the 21st century skills in teaching and learning to ensure career readiness among learners. Information Communication Technology tools provide the opportunity for educators to address problem-solving and project-based learning in both face-to-face and blended learning. However, there have been issues of educators’ awareness and skills in utilizing the technology tools in the instructional processes. This study attempts to explore the experience and awareness among lecturers to integrate computer-related technologies in undergraduate classrooms. In-depth semi-structured interviews were conducted with two lecturers who are experts in foreign language and one from Instructional Technology field. In-depth semi structured interviews and observations became the main qualitative instruments for this study. The purpose of the study sought to reveal the pedagogical approach and types of Information technology adopted in the classrooms. This study addressed their awareness and issues related to the use of technology in the classroom. The results were thematized based on Web 2.0 tools integration, pedagogical approach in addressing higher order thinking skills and student career readiness. Lecturers were found to be aware of the relevance of Web 2.0 tools for instructional purposes. However, they highlighted low internet speed as the main challenge in their efforts to integrate technology into their instructional activities. This research contributes to the area of TPACK (Technology Pedagogical Content Knowledge) by highlighting the application of computer-related technologies into classroom instruction and how such technologies are matched with learner-centered instructional strategies to enhance learners’ 21st century skills that are essential for career readiness.